Positive and Negative Effects of Research and Development - Shaari, Mohd Shahidan; Abdullah, Diana Nabila Chau; Alias, Nur Salimah; Adnan, Nor Syamimi Mohamed (International Journal of Energy Economics and Policy, 2016)
This study aims to examine the effects of research and development expenditure on economic growth and carbon dioxide emission in the panel data for the period of 1996-2011 from 5 nations (Germany, Russian Federation, United Kingdom, United States and Canada). The panel co-integration was conducted and the results show that there is co-integrated relationship among the variables (R&D, GDP, Energy Use and Carbon Dioxide Emission). Then the FMOLS test was performed and the findings explain that energy use and R&D are the determinants of GDP. Results from FMOLS show that energy use and R&D are the determinants of GDP. Energy use and GDP are the determinants of carbon dioxide emission. Results from DOLS show that R&D is important to boost economic growth while energy use, GDP and R&D can have deleterious effects on carbon dioxide emission. Therefore, it is important to control the R&D expenditure to balance economic growth and environmental conservation. Keywords: R&D, Economic Growth, Carbon Dioxide Emission JEL Classifications: O32, Q40, Q50